Tooth loss, denture use, and all-cause and cause-specific mortality in older adults: a community cohort study - Dai, Miao; Song, Quhong; Lin, Taiping; Huang, Xiaohong; Xie, Yufang; Wang, Xiang; Zheng, Liwei; Yue, Jirong (Frontiers in Public Health, 2023)
Objectives The available evidence on the connections between tooth loss, denture use, and mortality from all causes or specific causes among older adults is inconclusive. Therefore, we aimed to investigate the association between tooth loss, denture use, and all-cause and cause-specific mortality in older adults. Methods A cohort of 5,403 participants aged 65 and older were recruited in the 2014 Chinese Longitudinal Healthy Longevity Survey wave and followed up in the 2018 wave. Cox proportional hazard models were used to examine the association between the number of natural teeth, denture use, and all-cause and cause-specific mortality. Results During a mean (SD) follow-up of 3.1 years (1.3), 2,126 deaths (39.3%) occurred. Individuals with 0 and 1–9 teeth had higher mortality due to all-cause, cardiovascular disease (CVD), cancer, and other causes (all p-trend <0.05) than those with 20+ teeth. At the same time, no association was found with respiratory disease mortality. Participants who used dentures had lower mortality due to all causes [hazard ratios (HR) 0.79, 95% confidence intervals (CI) 0.71–0.88], CVD (HR 0.80, 95% CI 0.64–1.00), respiratory disease (HR 0.66, 95% CI 0.48–0.92), and other causes (HR 0.77, 95% CI 0.68–0.88) than those without dentures. Joint analysis revealed that older adults with fewer natural teeth and no dentures had higher mortality. Additionally, interaction analyses showed that the effects of the number of natural teeth on all-cause mortality were more pronounced in older adults aged <80 years (p-value for interaction = 0.03). Conclusion Having fewer natural teeth, particularly less than 10 teeth, is linked to an increased risk of mortality from all causes, including CVD, cancer, and other causes, but not respiratory disease. The use of dentures would mitigate the adverse impact of tooth loss on all-cause and some cause-specific mortality.